Overcoming Losses with the Application of the FIFO Method at MSME Partners Toko Senang Hati and Kios Rahmat - Bakade, Salwa; Wafa, Zaenal (Jurnal Pengabdian Masyarakat Bestari, 2024)
This service aims to help MSME partners of Toko Senang Hati and Kios Rahmat to reduce losses due to expired goods. The methods used are observation for introduction to the types and conditions of MSME partners, interviews to identify problems, socialization of the solutions offered, namely using the partners, socialization of the solutions offered, namely using inventory management with the FIFO method, training and assistance with help partners manage inventory of goods simply starting from making inventory cards and managing expiry dates, making inventory cards and grouping goods, finally an evaluation to determine the impact of the solution. To determine the impact of the solution and periodic evaluations are carried out. The result of this service, MSME partners of Toko Senang Hati and Kios Rahmat can find out how to manage inventory properly and correctly. How to manage inventory properly and correctly so as to reduce losses due to expired goods, losses due to expired goods.